Analysis Of Microturbine And Battery Storage System In Grid-Connected And Off-Grid Operations - Khamis, Alias; Mohd Aras, Mohd Shahrieel; Mohd Zambri, Mohd Khairi; Ab Ghani, Mohd Ruddin; Abdul Rahim, Mohd Nazarul Affan (Praise Worthly Prize, 2016)
-